Flexibilización y combinación de procedimientos en el sistema procesal civil brasileño - da Fonseca Gajardoni, Fernando (2025)
The authors analyze the Brazilian civil procedural system, specifically the principles of procedural adequacy and adaptability, flexibility, and the possibility of combining procedures, as generic powers of the judge. However, they emphasize their limits and the preservation of the parties' guarantees to promote legal certainty and avoid surprise decisions.